A rare blood moon over South Africa - Meel, Piyush (SA Heart Journal, 2025)
Photo: Courtesy of Dr Piyush Meel "A rare blood moon over South Africa during a total lunar eclipse, where Earth’s atmosphere refracts red light onto the Moon. Such events occur roughly every 2.5 years at a given location."